Reproductive seasonality and oviposition induction in trophon geversianus (gastropoda: Muricidae) from golfo Nuevo, Argentina - Cumplido Esmoris, Mariano José (2010)
The reproductive biology of a population of the edible muricid Trophon geversianus inhabiting an intertidal rocky shore in Golfo Nuevo (Chubut, Argentina) was studied regarding the seasonality of oviposition and oviposition induction under laboratory conditions. Sex ratio in the population differed from 1:1 (female biased). The mean shell length was 22 mm for males and 24 mm for females, although the females presented significantly larger maximum sizes. No external sexual dimorphism was evident, whereas the female snails differed internally by the presence of the albumin and capsule gland and by gonad color. Although the population under study inhabits an area with marine traffic and a concentration of 1.9 ng Sn/g, it did not present signs of imposex, in contrast with other sympatric species. T. geversianus presented a marked reproductive seasonality during the study period. Oviposition started in May and concluded in November, when hatching of crawling embryos was registered up to January. This seasonality coincided with changes in water surface temperature, ambient temperature, and photoperiod. Reproductive activities were registered when the environmental stress was minimum. In the aquarium, each female laid an average of 12 egg capsules (range, 626) per oviposition event, and needed a total of 25 h (range, 1257 h) to complete attachment of a single egg capsule. Data presented here could be useful for culture of the species.